Relationship of temporary blood glucose levels during pregnantcy and baby’s birth weight - Trimardiyah Trimardiyah; Fatimah Fatimah; Lia Dian Ayuningrum; Ika Sulistiowati (Alma Ata University Press, 2021)
Background : Blood sugar level is one of the factors that influence to baby’s birth weight which determines neonatal morbidity and mortality. Temporary blood glucose (GDS) includes the results of a momentary examination one day regardless of the time of the last meal. Data of baby’s birth weight in 2018 are 208 babies having BBLR, 32 babies having BBLB and 11 expectant mother diagnosed with gestational diabetes. Blood sugar check are often performed to diagnose a disease. From the results of the preliminary study at Panembahan Senopati Bantul Hospital, there was data about newborn start from January - December 2018. There were 208 (9%) babies having BBLR, 42 (1%) babies having BBLB, and 2026 (90%) babies born normally and 11 expectant mother diagnosed with gestational diabetes.Research Purpose : Knowing the relationship between temporary blood glucose level during pregnancy and baby’s birth weight at Panembahan Senopati Bantul Hospital.Research Method : This type of research is quantitative analysis with a retrospective study approach. The population are mothers in labor at Panembahan Senopati Bantul Hospital. The sampling method used nonprobability with purposive sampling technique. Statistical test used Spearman.Result : The majority of respondents had high school education (49%), aged between 20 - 35 (72%), Atem gestational age (80%), Paritas multipara (63%), normal LILA (90%), GDS not DM as much (57%) , there is no history of giving birth to large babies (82%), normal birth weight (37%), male gender (50%), and female (50%). There is a relationship between temporary blood glucose level during pregnancy and baby’s birth weight at Panembahan Senopati Bantul Hospital using the Spearman test with a p-value of 0.0001 which means significant (<0.05) and the result of the correlation coefficient (r) = 0.569 which means there is moderate or sufficient correlation.Conclusion : There is a significant relationship between temporary blood glucose level during pregnancy and baby’s birth weight at Panembahan Senopati Hospital, Bantul.